The simulation study of preheating temperature and blank thickness on hot press forming of aluminium alloy 6061 - Lai, Chee Fung (2022)
The need for affordable, lightweight materials rises in industrial applications. The problems of forming lightweight material are low formability and springback failure at room temperature. High-strength aluminium alloys offer lightweight properties due to their excellent formability at elevated temperatures and strength restoration after heat treatment. This numerical simulation study aims to develop a hot press forming (HPF) process model compared with the experimental result. The effect of preheating temperature and blank thickness on state variables was investigated based on the model constructed. Lastly, the grain transformation of the blank in the HPF was studied. DEFORM-3D simulation was used within this research to investigate the application of AA6061 on the HPF. Initially, a geometry model was constructed. The model has varied based on different preheating temperatures and blank thickness. The desired parameters were chosen for the subsequent grain analysis and blank temperature behaviour study. The results stated that 550 °C preheating temperature and 3 mm blank thickness were selected as the optimum process parameter to produce an ideal blank. The comparison was made between the simulation and experimental results; the maximum error obtained was 5.17%, considering the model chosen was valid. The grain study has found that as the quenching process took place, the grain amount and size would reduce. In conclusion, the findings have shown that the deformed blank quality was dependent on preheating temperature and blank thickness. The HPF process could alter and improve the grain distribution of the blank. DEFORM-3D can reveal the hidden phenomena and behaviours of forming AA6061 using the HPF process, which is challenging to identify by the experiments.